Teachers as School Mental Health Professionals and Their Daily Practices - Rojas-Andrade, R; Prosser-Bravo, G (Springer, 2024)
Despite the fundamental role of teachers in School Mental Health Systems, their work has been under-recognized and under-supported. Moreover, few studies on this role have been conducted in low- and middle-income countries. This study explores and describes the mental health actions undertaken by teachers in schools and categorizes them using latent class analysis. The study collected data from 726 teachers in Chile using snowball sampling. Three self-reported questionnaires were administered: Mental Health Actions and Teaching Role Questionnaire; Interprofessional Competence in Mental Health Questionnaire and Checklist of Mental Health Issues Addressed in School. The results showed that teachers play a significant role in identifying and addressing mental health issues among students, with 90% of respondents reporting that they had provided support to students with mental health concerns. The results also suggest that teachers face several challenges in this role, including a lack of training and resources, time constraints, and the need for better communication and collaboration with mental health professionals. Six latent class of teachers was founded: ow activity Class, Classroom-Centered Class, Individual Emotional Support-Centered Class, Self-Care and Professional Development Class, Mental Health Curriculum-Centered Class, and High activity Class. Based on the results provides applied recommendations for teachers to support their students mental health, such as creating a safe and supportive classroom environment, promoting social-emotional learning, and collaborating with specialised school mental health professionals. Overall, this study highlights the need for a comprehensive and integrated approach to school mental health that involves teachers, mental health professionals, and other stakeholders. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.